Masa ciała dzieci uczących się w podstawowych szkołach wiejskich a styl życia rodzin = The body weight of rural primary school pupils and the lifestyle of their families - Szadowska-Szlachetka, Zdzisława; Tarka, Magdalena; Ślusarska, Barbara; Łuczyk, Marta; Pietraszek, Agata; Łuczyk, Robert; Bartoszek, Agnieszka; Charzyńska-Gula, Marianna (Journal of Education, Health and Sport, 2016)
Szadowska–Szlachetka Zdzisława, Tarka Magdalena, Ślusarska Barbara, Łuczyk Marta, Pietraszek Agata,Łuczyk Robert, Bartoszek Agnieszka, Charzyńska-Gula Marianna. Masa ciała dzieci uczących się w podstawowych szkołach wiejskich a styl życia rodzin = The body weight of rural primary school pupils and the lifestyle of their families. Journal of Education, Health and Sport. 2016;6(9):546-553. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.154755 http://ojs.ukw.edu.pl/index.php/johs/article/view/3880 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.08.2016. Revised 25.08.2016. Accepted: 21.09.2016. Masa ciała dzieci uczących się w podstawowych szkołach wiejskich a styl życia rodzin The body weight of rural primary school pupils and the lifestyle of their families Zdzisława Szadowska–Szlachetka1, Magdalena Tarka2, Barbara Ślusarska3, Marta Łuczyk1, Agata Pietraszek1,Robert Łuczyk4, Agnieszka Bartoszek3, Marianna Charzyńska-Gula5 Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Absolwentka Wydziału Nauk o Zdrowiu, Uniwersytetu Medycznego w Lublinie Zakład Medycyny Rodzinnej i Pielęgniarstwa Środowiskowego, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Katedra Interny z Zakładem Pielęgniarstwa Internistycznego, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie Wydział Nauk Społecznych i Humanistycznych, Państwowa Wyższa Szkoła Zawodowa im. prof. S. Tarnowskiego w Tarnobrzegu Adres korespondencyjny: Zdzisława Szadowska-Szlachetka, Zakład Onkologii, Katedra Onkologii i Środowiskowej Opieki Zdrowotnej, Wydział Nauk o Zdrowiu, Uniwersytet Medyczny w Lublinie, ul. S. Staszica 4-6, 20-081 Lublin, tel. +48 81 448 6810, e-mail: zszadowska@wp.pl Streszczenie Cel pracy. Celem pracy była analiza masy ciała dzieci uczących się w szkołach wiejskich oraz stylu życia ich rodzin. Materiał i metoda. Badaniem zostało objętych 100 rodziców dzieci z klas I-VI uczących się w szkołach wiejskich w powiecie Opole Lubelskie. Metodą badawczą był sondaż diagnostyczny z użyciem techniki wywiadu przy zastosowaniu autorskiego kwestionariusza wywiadu. Wyniki. Wśród badanej grupy 65% dzieci miało prawidłową masę ciała, 18% dzieci miało niedowagę a 17% nadwagę. Wśród ojców dzieci z nadwagą występowała zależność bliska istotnej statystycznie p=0,06 dotycząca ich nadwagi. Nie występował związek istotny statystycznie między ilością posiłków a masą ciała dzieci. U części dzieci (około 20%) nadwaga występowała, gdy jako nagrodę za dobre zachowanie i wyniki w nauce dzieci otrzymywały słodkie przekąski oraz możliwość dodatkowego korzystania z komputera i telewizji. Z badań własnych wynika, że istnieje związek między codziennym piciem słodkich napojów gazowanych przez dzieci, a prawidłową masą ciała dziecka p=0,044. Większość badanych rodziców (83%) deklarowała, że ich dzieci uprawiają dodatkową aktywność fizyczną poza lekcjami wychowania fizycznego. Z analizy statystycznej wynika, iż nie występuje związek między sposobem spędzania wolnego czasu przez rodzinę (oglądanie telewizji, gry i zabawy na świeżym powietrzu, korzystanie z komputera, czytanie książek, wycieczki) a masą ciała dzieci w badanej grupie. Większość ankietowanych deklarowała, iż podczas spożywania posiłków zasiadała wspólnie przy stole. Wnioski. Nadwaga u dzieci ma związek z piciem przez nie słodkich napojów. Stosowanie nagród w postaci słodkich przekąsek, dodatkowego korzystania z TV i komputera, sposób spędzania wolnego czasu przez rodzinę i sposób spożywania posiłków nie ma związku istotnego statystycznie z masą ciała dzieci w badanej grupie. Słowa kluczowe. masa ciała, dzieci, szkoła podstawowa, styl życia, rodzice, BMI. Abstract Objective. The objective of the study was to analyse the body weight of rural school pupils and the lifestyle of their families. Material and method. The survey covered 100 parents of children from grades 1-6 of rural primary schools in the Opole Lubelskie District. The diagnostic survey with the interview technique was used as the research method, and a self-designed interview questionnaire was applied. Results. In the surveyed group the body weight of 65% of children was normal, 18% of children were underweight and 17% - overweight. Among the fathers of overweight children there was a correlation close to the statistical significance threshold, i.e. p = 0.06, referring to their overweight. There was no statistically significant connection between the number of meals consumed by the children per day and their body weight. In some children (approx. 20%) overweight occurred when, as a reward for good behaviour or grades, they received sweets or were allowed to use the computer or watch television. The self-designed survey results show a connection between daily consumption of sweet carbonated drinks by children and their body weight p = 0.044. Most of the surveyed parents, i.e. 83%, declared that their children undertook physical activity in addition to physical education classes. The statistical analysis demonstrates that there is no correlation between the way in which families spend their free time (watching television, games and playing outdoors, using the computer, reading books, trips) and the body weight of the children from the surveyed group. Most of the respondents stated that their families ate their meals together. Conclusions. Overweight in children is connected with the consumption of sweet drinks. Using rewards in the form of sweets, additional television and computer time, and also the way in which families spend their free time and eat their meals do not form a statistically significant correlation with the body weight of children in the analysed group. Key words. body weight, children, primary school, lifestyle, parents, BMI.